Impact of dental caries on their quality of life in preschools peruvians - Cosme, Tania (2019)
Objective: To determine the effect of dental caries on the quality of life of pre-school children. Materials and methods: The present was an observational, correlational, cross-sectional and prospective study in which 200 parents participated, who filled the ECOHIS questionnaire. Children were clinically evaluated using the ICDAS diagnostic criteria by a single examiner calibrated by a gold-standard, presenting an inter and intra-examiner Kappa of 0.79 and 0.81 respectively. The statistical analysis used was Chi square. Results: The impact of dental caries on quality of life using the ECOHIS questionnaire was considered intermediate. The parents' educational level did not show to be a variable that influenced their perception, and there were no statistically significant differences (p = 0.53). Regarding the prevalence of dental caries according to the ICDAS criterion was 94% if the WHO criteria is applied 82% of children showed dental caries. The mean d3-6mf-t of the population was 5.05, confirming that the disease was present in a high number of the examined children aged 3 to 5 years. Conclusions: Despite a high prevalence of dental caries in children, this condition had a medium impact on their Oral Health Related Quality of Life, according to the perception of their parents.